RANCANG BANGUN MESIN PENCETAK BRIKET - Fatjri Novianti; Krisna Raden; Dino Arisandi; Muhammad H Amrullah; Pristiansyah Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The development of technology in the production sector is very rapid, one of which is in the production of Charcoal Briquettes. Charcoal briquettes are solid materials that contain carbon, have a high calorific value, and can burn for a long time. Charcoal briquettes made from coconut shell charcoal currently contribute to reducing dependence on oil and gas fuels and are able to meet export needs to various countries. SMEs in the area of Jelitik Village, Sungailiat District, Bangka Regency need a charcoal briquette printing machine to process coconut shells. Therefore, the authors design and manufacture a charcoal briquette printing machine with the aim of accelerating the production process and improving the quality of charcoal briquettes with mixed ingredients (starch flour, water, and coconut shell charcoal). The method of design and manufacture of Charcoal Briquette machine refers to VDI 2222. From the steps of the method carried out, the design of the Charcoal Briquette machine is obtained with 3 systems, namely stirring, printing and cutting.The results of the tests carried out were observing  the machine operating well or not, if it was good then the briquette printing test  with the output of the briquettes had good quality and was not easily broken with a production time of 10/hour.